Lung function associated gene Integrator Complex subunit 12 regulates protein synthesis pathways - Kheirallah, Alexander K.; de Moor, Cornelia H.; Faiz, Alen; Sayers, Ian; Hall, Ian P. (BioMed Central, 2017)
Background Genetic studies of human lung function and Chronic Obstructive Pulmonary Disease have identified a highly significant and reproducible signal on 4q24. It remains unclear which of the two candidate genes within this locus may regulate lung function: GSTCD, a gene with unknown function, and/or INTS12, a member of the Integrator Complex which is currently thought to mediate 3’end processing of small nuclear RNAs. Results We found that, in lung tissue, 4q24 polymorphisms associated with lung function correlate with INTS12 but not neighbouring GSTCD expression. In contrast to the previous reports in other species, we only observed a minor alteration of snRNA processing following INTS12 depletion. RNAseq analysis of knockdown cells instead revealed dysregulation of a core subset of genes relevant to airway biology and a robust downregulation of protein synthesis pathways. Consistent with this, protein translation was decreased in INTS12 knockdown cells. In addition, ChIPseq experiments demonstrated INTS12 binding throughout the genome, which was enriched in transcriptionally active regions. Finally, we defined the INTS12 regulome which includes genes belonging to the protein synthesis pathways. Conclusion INTS12 has functions beyond the canonical snRNA processing. We show that it regulates translation by regulating the expression of genes belonging to protein synthesis pathways. This study provides a detailed analysis of INTS12 activities on a genome-wide scale and contributes to the biology behind the genetic association for lung function at 4q24.